BLRI-IRRI Collaborative Activities on Fodder Production and Native Chicken Demonstration in 2024 - Sultana, Nasrin; Hasan, Shamim; Islam, Tarequl; Miajy, Abdullah; Debnath, Manik; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
Livestock is an integral and indispensable component of the agricultural system in Bangladesh. Crop-livestock integration is one of the most efficient ways, where livestock are utilized mainly agricultural by-products and provide human nutrition security through milk and meat, serve as savings accounts for the farmers, and provide manure, considered a high-quality fertilizer for maintaining optimum soil health. Therefore, the concept of a mixed farming system (MFS) becomes increasingly significant in sustainable agriculture since this system ensures minimal wastage by utilizing the by-products of one system as inputs for others. Mixed farming systems that incorporate environmentally friendly and cost-effective practices for efficient water, soil, crops, and pest management are essential for achieving sustainable development in agriculture. Mixed farming systems have been demonstrated to be more efficient than specialized crop or livestock production systems. According to Kumar et al. (2017), MFS promotes social, economic, and environmental sustainability in addition to assisting in the security of food, nutrition, and livelihood. The International Rice Research Institute has been implementing the CGIAR research initiative on Mixed Farming Systems (MFS) in Bangladesh since 2022. International Rice Research Institute (IRRI) and Bangladesh Livestock Research Institute (BLRI) started working together on the Mixed Farming System (MFS) project through a LoA. The project activities were started in the northern part (Rangpur & Nilphamari) in December 2022 and the southern part (Patuakhali) in June 2023. In this project, BLRI provided livestock-related technical assistance for implementing improved mixed farming systems (integration of crop and livestock) in the northern and southern regions of Bangladesh. In addition, the BLRI provided their developed native chickens to 20 farm households as a suitability test and performance evaluation. The ultimate goal of BLRI for this project is the improvement of livestock productivity through ensuring optimum nutrition and the development of fodder entrepreneurs/nurseries for its quick dissemination. This report is prepared by BLRI and submitted to IRRI as per the reporting schedule of the LoA in 2024.